Integrating atmospheric deposition, soil erosion and sewer transport models to assess the transfer of traffic-related pollutants in urban areas. (October 2017) - Hong, Yi; Bonhomme, Celine; Bout, Bastian Van den; Jetten, Victor; Chebbo, Ghassan
Abstract: For the first time, this paper develops an integrated and spatially-distributed modelling approach, linking atmospheric deposition, soil erosion and sewer transport models, to assess the transfer of traffic-related pollutants in urban areas. The modelling system is applied to a small urban catchment near Paris. Two modelling scenarios are tested by using experimentally estimated and simulated atmospheric dry deposits. Simulation results are compared with continuous measurements of water flow and total suspended solids (TSS) at the catchment outlet. The performance of water flow and TSS simulations are satisfying with the calibrated parameters; however, no significant difference can be noticed at the catchment outlet between the two scenarios due to the "first flush" effects. Considering the Cu, BaP and BbF contents of different particle size classes, simulated event mean concentration of each pollutant is compared with local in-situ measurements. Finally, perspectives to improve model performance and experimental techniques are discussed. Highlights: An integrated and spatially-distributed air-surface-sewer model is developed. Modelling the transfer of traffic-related pollutants in urban areas. Simulations of TSS concentrations fit well with the continuous measurements. Realistic simulations of Cu, BaP and BbF are achieved at the catchment outlet.